THE STATE OF DEVELOPMENT OF INTERNATIONAL BUSINESS IN CRISIS CONDITIONS IN UKRAINE - Oksana Melnichuk (Izdevnieciba "Baltija Publishing", 2021)
The subject of the study is a set of basic theoretical, scientific and methodological provisions and practical recommendations for analyzing trends in the system of international business and increase the effectiveness of institutional support for enterprises participating in international business. In the course of the research such concepts as "foreign economic activity", "international entrepreneurship", "international business" are considered. The latter is proposed to be considered as a system of business processes implemented by business entities outside of their own country and aimed at achieving strategic goals. Research methods. General scientific and special methods are used in the work, which allow to systematically solve problem tasks in the chosen direction of the research. In the course of the research such methods are used as: method of theoretical generalization; system analysis; graphic and analytical methods. Results. An analysis of the impact of the coronavirus pandemic on the activities of international market players has been made. A comprehensive analysis of the volume, commodity, geographical structure of exports and imports of goods in Ukraine in 2018-2020. It is determined that Ukraine overwhelmingly exports raw materials and imports high-tech goods. Despite the decline in foreign trade, the general trend indicates that exports and imports will grow in the long run. An objective analysis of the functioning of the Ukrainian business system with the help of many world ratings, which allow us to assess the place of Ukraine in the global conditions of development, in comparison with the economies of other countries. As a result of the study, it was determined that Ukraine is inferior to other countries in the world in trade, regulatory policy, national branding, etc., and has the best position in the field of budget transparency. The results of the analysis indicate the need to implement effective organizational and economic principles aimed at improving the quality of Ukraine's business system. The analysis and construction of the profile of the national business system allowed to identify the main problems in the system of international business and begin to form measures to address them. The practical significance of the obtained results is that the theoretical provisions and practical recommendations obtained by the author as a result of the study can be used in developing directions for the transformation of national international business in a crisis.